Opioid Prescription Patterns for Discharged Patients from the Emergency Department. (19th January 2021) - Yanuck, Justin; Lee, Jonathan B.; Saadat, Soheil; Rouhi, Jila; Ghanem, Ghadi; Chakravarthy, Bharath; Shah, Shalini
Abstract : Context . Opioid prescriptions from the emergency department (ED) have gradually increased over the last 20 years. Mounting evidence of the potential for abuse of these drugs, even after a transient ED encounter, has fueled a push to curtail the prescriptions of opioids from the ED. Objectives . It is important to analyze the types of etiologies and provider demographics that drive opioid prescription in our emergency departments. Our study aimed to determine which patients in the ED are receiving opioid prescriptions, as well as their strength and quantity. Secondary outcomes included identifying difference in prescribing between provider classes. Methods . We conducted a retrospective study at a tertiary care university-based, level-one trauma ED from November 2017 to October 2018. We identified and analyzed data from 2, 259 patients who were sent home with an opioid prescription. We retrieved patient and provider demographics, diagnosis, etiologies, and prescription information. Results . The mean age of a patient receiving an opioid prescription was 45, and 72.7% of patients were white. The most common diagnosis groups associated with an opioid prescription were abdominal pain (18.5%), nonfracture extremity pain (18.4%), and back/neck pain (12.5%). Hydrocodone-acetaminophen 5–325 mg was the most commonly prescribed (67.4%). The median total prescribed milligram morphine equivalent (MME) was highest for extremity fracture (75.0; IQR 54.0–100.0). The median total prescribed amount of pills was highest for patients with extremity fractures (15.0; IQR 12.0–20.0). Conclusions . Our study elucidates the prescribing patterns of an academic level 1 trauma center and should pave the way for future studies looking to maximize effectiveness at ways to curb ED opioid prescription.